Evaluation of Employee Payroll Decision-Making System at PT Morich Indo Fashion using Machine Learning - Efaforito Gulo; Yoannes Romando Sipayung (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
PT Morich Indo Fashion is a company that focuses on clothing production and includes fabric inspection, accessories, and heat transfer storage. This study aims to evaluate the use of payroll information systems in internal control. The method used in this research is descriptive with a qualitative approach, and the data obtained comes from secondary and primary sources. The problem faced by the Cooperative is that there are errors in calculating employee salaries and lack of clarity in the payroll process, where employees are only told the total amount of salary each month without knowing the amount of deductions caused by lateness or absenteeism in a month. To overcome this problem, a web-based payroll information system is needed. This research aims to design and develop a web-based employee payroll system at PT Morich Indo Fashion, with the aim of speeding up and simplifying the salary payment process effectively. This research uses a qualitative method with the Design and Creation approach and applies the waterfall development method. Testing is done with White-box Testing and Black-box Testing techniques. The results of the test show that the objectives of this research have been achieved. This application successfully simplifies and accelerates the process of calculating employee salaries in a transparent, accurate, effective, and efficient way.